2011
DOI: 10.1186/1472-6882-11-94
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edible bird's nest (EBN) on cultured rabbit corneal keratocytes

Abstract: BackgroundThere has been no effective treatment or agent that is available for corneal injury in promoting corneal wound healing. Previous studies on edible bird's nest extract (EBN) had reported the presence of hormone-like substance; avian epidermal growth factor that could stimulate cell division and enhance regeneration. This study aimed to investigate the effects of EBN on corneal keratocytes proliferative capacity and phenotypical changes.MethodsCorneal keratocytes from six New Zealand White Rabbits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…The proteoglycans isolated contained 83% carbohydrates, of which 79% were GalNAc and GlcUA (D-glucuronic acid) in an equimolar ratio. Recently, hot-water extraction of EBN showed the ability to promote cornea cells proliferation and cornea wound healing [17]. To date, all the previous studies demonstrated the beneficial effect of EBN extract prepared by water extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The proteoglycans isolated contained 83% carbohydrates, of which 79% were GalNAc and GlcUA (D-glucuronic acid) in an equimolar ratio. Recently, hot-water extraction of EBN showed the ability to promote cornea cells proliferation and cornea wound healing [17]. To date, all the previous studies demonstrated the beneficial effect of EBN extract prepared by water extraction.…”
Section: Introductionmentioning
confidence: 99%
“…1,9,10 Recently, some plant compounds, such as Astragalus membranaceus and Rehmannia glutinosa, have also been regarded as new supplements for different diseases, enhancing fibroblast proliferation in wound healing, 11,12 Sinomenine has an anti-inflammatory function. 13 Noticeably, various polyphenolic compounds from plants have been confirmed to have different pharmaceutical functions. 14,15 Previous studies show that: high molecular weight polyphenol from black tea can reverse the epithelialemesenchymal transition of human oral cancer cells 16 ; polyphenols extracted from pu-erh tea or blueberry regulate the proliferation and differentiation of 3T3-L1 preadipocytes 17,18 ; tea polyphenol has an antioxidant function and induces neuron-like differentiation of mesenchymal stem cells 19 ; and polyphenol-rich strawberry extracts increase mitochondrial activity and regenerative capacity for cells.…”
Section: Introductionmentioning
confidence: 99%
“…This remedy is used for several purposes like dissolving phlegm, voice improvement, libido raising, gastric problems, renal dysfunctions, asthma, cough and tuberculosis to name but a few in Chinese medicine and cuisine [13]. In past decades, scientists have shown many properties of EBNs such as cell proliferation induction by epidermal growth factor (EGF) like components, immunomodulatory effects such as decrease of TNFα and nitric oxide (NO) generation in RAW cells, improvement of corneal keratocyte proliferation which can be helpful in wound healing, neuroprotective activity against 6-hydroxydopamine (6-OHDA)-induced degeneration of dopaminergic neurons, improvement of bone strength and skin thickness, chondro protective properties by reduction of catabolic activities and potential antiviral activity against influenza viruses [8, 10, 1418]. Despite of these studies, potential bioactivities of EBN’s components require subsequent researches and characterization of the mechanisms of action that can provide valuable information on their usage in orthodox medicine.…”
Section: Introductionmentioning
confidence: 99%